Evaluation of the Implementation of Internal Control in the Project Budget Realization of PT ABC (E-Jurnal Akuntansi, 2026)
PT ABC, engaging in solar power plants, faces obstacles in project budget realization due to weak internal control. This study aims to evaluate the effectiveness of internal control in project budget realization at PT ABC. Internal control plays an important role because weaknesses in this process can cause operational and financial losses. This study uses a qualitative method with a case study approach that focuses on identifying risks and control activities. Research data was obtained through semi-structured interviews with management and analysis of company documents. The results of the study indicate that PT ABC's internal controls still have a number of weaknesses, mainly due to the lack of a systematic risk register and adequate SOPs to support each stage of budget realization. This condition indicates that the risk identification and mitigation processes are not yet optimal in order to PT ABC needs to develop a risk register, establish written procedures, and strengthen inter-division coordination.
Keywords: Internal Control; COSO; Budget Realization; PLTS